3D investigation of natural convection of nanofluids in a curved boundary enclosure applying lattice Boltzmann method. Issue 8 (20th September 2018) - Hosseini Abadshapoori, Mehdi; Saidi, Mohammad Hassan
Abstract : Purpose: The purpose of this paper is to investigate the natural convection behavior of nanofluids in an enclosure. The enclosure is a 3D capsule with curved boundaries filled with TiO2 -water nanofluid. Design/methodology/approach: In this paper, a multiple relaxation times lattice Boltzmann method (MRT-LBM) has been used. Two-component LBM has been conducted to consider the interaction forces between nanoparticles and the base fluid. Findings: Results show that the enhanced Nusselt number (Nu*) increases with the increase in volume fraction of nanoparticles ( ϕ ) and Ra number and decrease of nanoparticle size ( λ ). Additionally, the findings indicate that increasing volume fraction beyond a certain value decreases Nu*. Originality/value: This paper presents a MRT model of lattice Boltzmann in a 3D curved enclosure. A correlation is also presented based on the current results for Nu* depending on Ra number, volume fraction and size of nanoparticles. Furthermore, a comparison for the convergence rate and accuracy of this model and the SIMPLE algorithm is presented.